Le conseguenze grammaticali della perdita di -s in ladino - Salvi, Giampaolo (Italogramma, 2020)
<span dir="ltr" style="left: calc(var(--scale-factor)*111.62px); top: calc(var(--scale-factor)*156.28px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912724);" role="presentation">After briefly presenting and commenting on Saussure’s co<span dir="ltr" style="left: calc(var(--scale-factor)*398.23px); top: calc(var(--scale-factor)*156.28px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.920052);" role="presentation">ncept of diachronic <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*170.08px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.915695);" role="presentation">change, the study shows the validity of one of his intuitions through the analysis of lazy <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*183.88px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.902384);" role="presentation">concord phenomena in some Ladin dialects: a phonetic change, the loss of final <span dir="ltr" style="left: calc(var(--scale-factor)*455.62px); top: calc(var(--scale-factor)*183.88px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.8628);" role="presentation">-s <span dir="ltr" style="left: calc(var(--scale-factor)*467.26px); top: calc(var(--scale-factor)*183.88px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.884254);" role="presentation">before a <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*197.68px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.905631);" role="presentation">consonant inside the noun phrase, not only restructured the rules for plural concord in <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*211.48px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.905005);" role="presentation">feminine noun phrases, but also permitted the morphological expression of such syntactic <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*225.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.917826);" role="presentation">relations that formerly had remained implicit, and introduced agglutinative features in a <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*239.11px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.917287);" role="presentation">basically flectional language.